The science of stuck : breaking through inertia to find your path forward / $c Britt Frank, LSCSW. - Frank, Britt (TarcherPerigee, 2023)
"We all experience stuckness at some point in our lives -- in relationships, career paths, body struggles, addition issues, and more. Many of us know what we need to do to move forward, but find ourselves unable to take the leap to make it happen. The good news is that you're not lazy, crazy, or unmotivated. In this empowering and action-oriented guide, you'll discover why we can't think our way out of it -- and how to break through. Using an eclectic and science-based approach, this book is a hands-on road map for moving forward with purpose, confidence, and the freedom to become who you're truly meant to be." -- back cover.